Analysis of E-Commerce Utilization in Consumers as Culinary MSMEs in East Jakarta - Rahma Alia; Rutinaias Hoholongan; Erlangga Aldi Pratama; Maulana Akbar; Muhammad Arifin Alfaqih; Herlando Hosea Alang; Zulfikar Zulfikar (INCOME: Innovation of Economics and Management, 2024)
The purpose of this study research is to analyze the use of E-Commerce in consumers MSMEs which is based on the current development of globalization and its impact on technological progress and economic income. Analysis used to identification of the internal and external environment of culinary MSMEs. The Analysis we use in the study is qualitative research combined with descriptive analysis of the depiction of the object study in depth. So, a depiction of the object study can be provided. This data collection method is through survey information, and interviews. The results of this research show that e-commerce can provide broader information about culinary MSME products. An E-commerce system can also be a promotion for culinary MSME business actors to the establishment of buying online.